2021
DOI: 10.1108/ijmce-12-2020-0088
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring dyads in higher education: It feels lucky, but it's more than luck

Abstract: PurposeThe purpose of this paper is to explore the formation, maintenance and sustenance of a mentoring dyad in higher education. By investigating the reflections of a female mentor and mentee, who both engaged in a formal Mentoring Program, the intention is to inform the design of future programs and expectations of participants, enhance the quality of future practice and understand the benefits mentoring might offer to the academic community.Design/methodology/approachThe researchers utilised a self-study re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
3
0
1
Order By: Relevance
“…The study confirmed past research that found mentoring relationships are beneficial in the process of acclimation to the academy [4]. The results also extended research in relational leadership to include mentoring relationships [14,26,[34][35][36]. Characteristics of relational leaders include an emphasis on communication, social interactions, networking, and developing self-confidence in others, and the narrative comments demonstrated a strong preference for mentors who possess these characteristics.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The study confirmed past research that found mentoring relationships are beneficial in the process of acclimation to the academy [4]. The results also extended research in relational leadership to include mentoring relationships [14,26,[34][35][36]. Characteristics of relational leaders include an emphasis on communication, social interactions, networking, and developing self-confidence in others, and the narrative comments demonstrated a strong preference for mentors who possess these characteristics.…”
Section: Discussionsupporting
confidence: 84%
“…Mentoring in higher education is intuitive as it presents an extension of the learning process itself. The value of mentoring academics at all levels is noted by the literature [14] and can be rewarding and fulfilling for both mentor and protégé [3]. Faculty mentoring other faculty leads to increased employment satisfaction as well as improved outcomes for promotion and tenure for the individuals [3].…”
Section: Mentoring and Higher Educationmentioning
confidence: 99%
“…En esta línea se valora especialmente el intercambio y estudio conjunto y socialización de experiencias entre pares, porque permite a las y los docentes reflexionar sobre las acciones de otros y, a la vez, apropiarse de iniciativas profesionalmente interesantes (Padilla & Madueño, 2019). Por último, cabe destacar también la incorporación de la observación de clases, el uso de videos y feedback entre pares, que contribuye de manera fundamental al desarrollo académico y a la reflexión de la propia práctica (Fitzgerald & McNamara, 2021;Miranda et al, 2021;Wass & Rogers, 2021).…”
Section: Discussionunclassified
“…As a result, most educational institutions in the world employ mentorship programs to suit their objectives as well as workers' developmental requirements. In the higher educational system, mentoring has been found to support staff development and learning (Fitzgerald and McNamara, 2021;Searby et al, 2015). With global competition in university ranking (Jones and Smith, 2022), rapid technological changes, the question of teaching and learning excellence (Stevenson et al, 2017), constrained resources, inadequate infrastructure, and incessant industrial stalemate amongst other challenges, higher educational institutions are always looking for methods to achieve so much with so little.…”
Section: Introductionmentioning
confidence: 99%